Robert Penn Warren's All the King's Men : A Reader's Companion - Cullick, Jonathan S. (Book collections on Project MUSE., 2018)
Robert Penn Warren is one of the best-known and most consequential Kentucky writers of the twentieth century and the only American writer to have won three Pulitzers in two different genres. All the King's Men, generally considered one of the finest novels ever written on American politics, transcends sensationalism and topicality to stand as art. It was a bestseller, won the Pulitzer Prize, and became an Academy Award--winning movie. Depicting the rise and fall of a dictatorial southern politician -- modeled on Huey Long of Louisiana -- the timeless story and memorable characters raise questions about the importance of history, moral conflicts in public policy, and idealism in government. In Robert Penn Warren's All the King's Men: A Reader's Companion, author Jonathan S. Cullick considers the themes of this famous novel within the context of America's current political climate. He addresses the novel's continuing relevance and interviews a cross-section of elected and appointed officials, as well as journalists, in Kentucky to explore how Warren's novel has influenced their work and approach to politics. By focusing on what Warren's novel has to say about power, populism, ethics, and the force of rhetoric, Cullick encourages readers to think about their own identities and responsibilities as American citizens. This volume promises to be not only an indispensable companion to All the King's Men but it also provides context and a new diverse set of perspectives from which to understand this seminal novel.